REFORM TYPES OF LEGISLATION REGULATIONS IN INDONESIA: REFORMULASI JENIS PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Haryadi Haryadi; Muhammad Syafei; Muhammad Rafi Darajati (Constitutional Law Society, 2022)
The arrangement of the types and hierarchies of statutory regulations has been confirmed in Article 7 paragraph (1) of Law Number 12 of 2011. In addition to the provisions of Article 7 paragraph (1), it is also regulated in Article 8 paragraph (1) of the types of laws and regulations established by institutions/agencies/commissions. In Article 8 paragraph (2), it is emphasized that the laws and regulations as referred to in Article 8 paragraph (1) are recognized to exist and have binding legal force as long as they are ordered by more comprehensive legislation high or formed by authority. The expansion of the types of laws and regulations, as confirmed in Article 8 paragraph (1), if it is associated with the provisions of Article 7 paragraph (1), will cause problems. Whether the hierarchical provisions of the legislation in Article 7 paragraph (1) also applies to the provisions of Article 8 paragraph. This research aims to conduct a juridical analysis of whether the laws and regulations in Article 7 paragraph (1) of Law No. 12 of 2011 also apply to the provisions of Article 8 paragraph (1) of Law Number 12 of 2011. Thus, according to the author, the requirements of the hierarchy of laws and regulations as regulated in article 7 paragraph (1) cannot be applied to the laws and regulations stipulated in article 8 paragraph (1). The role of laws and regulations is critical to creating and maintaining harmonization and synchronization of laws and regulations in the sense that their types and hierarchies must be arranged. Hence, there are no conflicts in their implementation.